2020
DOI: 10.2485/jhtb.29.9
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Promotes Inflammation in Human Dental Pulp

Abstract: Macrophage migration inhibitory factor (MIF) has emerged as an essential proinflammatory cytokine in inflammatory and immune responses. We investigated the expression of MIF in human dental pulp tissue and the function of MIF in human dental pulp fibroblast-like cells. MIF was expressed in areas of dental pulp characterized by a robust inflammatory response, for instance, in human dental pulp tissues that exhibited pathological signs of purulent inflammation. MIF stimulated the expression of prostaglandin-endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Inflammation promotes nearly all stages of OSCC carcinogenesis and progression (3). Recent studies have indicated that macrophages and relevant cytokines are involved in inflammation (4,5). TAM-associated cancer inflammation regulates tumor growth and progression via various mechanisms, depending on the type and frequency of released tumor-derived factors (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation promotes nearly all stages of OSCC carcinogenesis and progression (3). Recent studies have indicated that macrophages and relevant cytokines are involved in inflammation (4,5). TAM-associated cancer inflammation regulates tumor growth and progression via various mechanisms, depending on the type and frequency of released tumor-derived factors (6,7).…”
Section: Introductionmentioning
confidence: 99%